A comparative cross-sectional study of the impact of COVID-19 pandemic on obstetrics and gynecology admissions in Croatia - Kalanj, Karolina; Mikuš, Mislav; Peček, Mirta; Orbanić, Ante; Marshall, Rick; Orešković, Stjepan; Orešković, Slavko (Frontiers in Medicine, 2025)
BackgroundThe COVID-19 pandemic placed unprecedented pressure on healthcare systems worldwide and altered patients' perceptions of the system's ability to protect them from virus transmission. One significant consequence was a marked decline in hospital activity, a trend observed globally. This study aims to evaluate the impact of COVID-19 on hospitalization rates among patients with gynecological disorders in Croatia. It compares the number of patients treated surgically vs. conservatively before the pandemic (2017–2019) and during the pandemic (2020–2022) using the Diagnostic-Related Group (DRG) patient classification system. The DRG system is designed to group patients based on similar clinical conditions, complexity, and resource utilization. Hospital activity categorized by DRGs was analyzed to assess the impact of the COVID-19 pandemic on case volumes within DRG groups associated with gynecological and obstetric disorders.Materials and methodsWe conducted a comparative descriptive cross sectional study of the pre-post type according to STROBE guidelines to determine the impact of COVID-19 pandemic on hospital admission rates for patients with conditions associated with illnesses and abnormalities of the female reproductive system, as well as pregnancy, delivery, and the puerperium. The publicly available data collected by Croatian Institute of Public Health (CIPH) and the Croatian Health Insurance Fund (CHIF) were the main data source for this study. All gynecological hospital admissions in Croatia were grouped based on the Australian Refined Diagnosis Related Groups (AR-DRGs) and analyzed over two time periods: before (2017–2019) and during the pandemic (2020–2022).ResultsThe average number of gynecological patients in all hospitals during the pandemic was 62,257 compared to pre-pandemic when the average number of patients was 71,519, a decrease of 15.5%. The results show a 10.56% decrease in the total number of non-surgical admissions and 12.8% decrease of surgical admissions across the hospital network during the pandemic (2020–2022).ConclusionThe COVID-19 pandemic led to a significant decline in inpatient treatments in gynecology and obstetrics departments in Croatia. Our findings highlight the need for obstetrics and gynecology practitioners to develop innovative strategies to maintain or enhance patient access to appropriate care while ensuring stringent infection prevention measures for both patients and healthcare personnel. Furthermore, investing in healthcare system resilience is crucial to maintaining core functions during future crises. The lessons learned from the COVID-19 pandemic provide a valuable opportunity to fortify healthcare systems and must not be ignored.